Analisis Tarif INA-CBGS Kasus Persalinan dengan Penyulit Disertai Prosedur Sectio caesarea - Azizzulida, Cut Adiba; Saptorini, Kriswiharsi Kun (Politeknik Negeri Jember, 2025)
Financing for Sectio caesarea (SC) procedures within the INA-CBGs system is determined based on specific medical indications. When discrepancies arise between INA-CBGs reimbursement rates and hospital service rates, hospitals may experience financial losses. This study aims to describe INA-CBGs tariffs across various severity levels by considering the characteristics and clinical conditions of delivering mothers. This research employed a descriptive quantitative design. The researcher observed 142 claim data entries for complicated deliveries involving SC procedures, and the data were analyzed descriptively. The results showed that most patients were aged 26–30 years (34.51%), had a medical indication of previous SC (27.46%), were treated in class III wards (54.93%), had a length of stay of four days (66.90%), had a primary diagnosis of O34.2 (31.69%), and were categorized as severity level I (76.06%). The most common secondary diagnoses were a history of SC (12.37%) and anemia (12.37%). Hospital tariffs varied considerably, and the deficit between INA-CBGs rates and hospital rates reached approximately 40 million rupiah. Hospitals should implement strict internal validation of claims, ensure complete documentation, strengthen inter-unit coordination, and provide regular training for staff on updated claim regulations.